Distribution and reserves polygonum minus huds in almaty region (Eurasian Journal of Ecology, 2016)
Authors have studied two populations of Polygonum minus Huds. in Enbekshikazakh district of Almaty region. Population number 1 was found on the territory of the Komsomol pond below village Kosmos (south shore), the coordinates N 43030.561´ and E 077014.815’, altitude 589 m Vegetation population was represented Polygonum minus, Polygonum amphibium – Xanthium strumarium association, projective coverage of 100%, the alluvial-meadow soil. Population 2 was found in wetlands near the river Zharsu along the road from the village Kazatkom to the villageKoldey (Prudhoz), coordinates N 43038.227´ and E 077048.441´; altitude 523 m, the vegetation was represented by Polygonum minus, Polygonum scabrum, Polygonum hydropiper – Eleoharis finica – Deschamsia caespitosa, Hordeum brevsubulatum, Echinochloa crusgalli association. Projective cover of 100%, the alluvial meadow marsh soil. The aimof study was to investigate floristic composition of the vegetation and the definition of reserves medicinal vegetative raw materials of Polygonum minus. Description of vegetation was conducted in accordance with generally accepted methods of Geobotany and definition reserves of medicinal plants (bush area, yield and possible yearly harvest) wasconducted according to the methods A.I. Schreter, A.I. Polozhij, L.P.Ashmarina. Geobotanical and floristic descriptions of plant communities of two populations of Polygonum minus were conducted and its medicinal raw stocks in the Almaty region were established as a result of these studies.
Keywords: Polygonaceae Juss; Polygonum minus Huds; дәрілік өсімдік; өсімдіктер қауымдастығы; шикізат қоры; Polygonaceae Juss.; Polygonum minus Huds.; лекарственное растение; растительная ассоциация; запасы сырья.